The mediating effect of IT capability on the relationship between TQM and MO with microfinance institutions performance - Homaid, Abdo Ali Abdullah (2016)
Microfinance, an effective tool to fight poverty and economic development, has attracted the attention of governments, international organizations, and academicians across the globe. Although the literature confirms on the significant effect of Total Quality Management (TQM), Market Orientation (MO), and Information Technology (IT) on MFIs performance, research done on the relationships between these factors is still insufficient. This study aims to examine the interaction effects of TQM, MO, and IT capability on MFIs performance and thus, provide additional insights into the literature. It also examines the mediating effect of IT capability on the relationship between TQM and MO with the MFIs performance. The study employs Resource-Based View as the guiding theory with two supporting theories, namely, Dynamic Capability Theory and Complementarity Theory. Cross-sectional survey was employed, and questionnaires were administered to collect data from the branch managers in Yemen. Out of 166 questionnaires distributed through a self-administered approach, 125 usable responses were used for the analysis. Partial Least Square-Structural Equation Modeling was advocated and the result provides an empirical evidence of the significant effect of TQM, MO and IT capability on the MFIs performance. More important, this study reveals that IT capability is a significant mediator on the relationship between TQM, MO and MFIs performance, and hence supporting the theoretical premises. The study concludes with the theoretical contributions, managerial implications on MFIs, limitations of the study and suggestions for future research.